SPATIAL VARIABILITY OF THE PROPERTIES OF COHESIVE SOILS FROM EASTERN MARANHAO, BRAZIL - Amaral Resende, Jose Maria do; Marques Junior, Jose [UNESP]; Martins Filho, Marcilio Vieira [UNESP]; Dantas, Jussara Silva; Siqueira, Diego Silva; Teixeira, Daniel De Bortoli [UNESP] (Soc Brasileira De Ciencia Do Solo, 2014)
The national and international demand for maps of soil properties has increased. The aim of this study was to characterize cohesive soils and associate their variability of particle size, chemical properties, and color to different landforms in agricultural areas and native vegetation using geostatistical techniques. To set up the experiment, we selected three areas of soil consisting of an area planted to soybeans and, contiguous to it, another area with plant cover remaining from three types of cerrado (tropical savanna), designated Cerradao (A), Cerrado (B), and Campo Cerrado (C). The areas A and B are located on a concave landform, while area C is on a convex landform. Sampling grids with 121 points were established in each area, and in areas with native vegetation, transects were constructed with five points spaced at 20 m. The largest mean ranges, considering both depths evaluated, were found for area A, with 115 m for particle size, 157 m for chemical attributes, and 168 m for soil color. Area B had mean ranges of 95, 64, and 160 m for grain size, chemical attribute, and soil color, respectively. For its part, area C exhibited the mean ranges of 63, 65, and 58 m in grain size, chemical attributes, and soil color, respectively. The environment with the greatest variability (area C) is related to locations with the occurrence of Campo Cerrado vegetation and a convex landform. This same site had the lowest responsiveness to soybean crop management, shown by soil fertility indicators for this crop, especially the low values for organic matter (9.20 mg kg(-1)) and CEC (29.60 mmol(c) dm(-3)). Thus, it can be stated that for the geological compartment studied, the environments of high variability will always be associated with areas with lower response to soil management for soybean.
Keywords: geostatistics; diffuse reflectance spectroscopy; savanna